A review of waste management in Brazil and Portugal: Waste-to-energy as pathway for sustainable development. (November 2021) - Ferraz de Campos, Victor Arruda; Silva, Valter Bruno; Cardoso, João Sousa; Brito, Paulo S.; Tuna, Celso Eduardo; Silveira, José Luz
Abstract: In this study, projections and current status of municipal solid waste generation worldwide and its collection, final destination, and waste-to-energy technologies are reviewed. Firstly, an overview of waste generation worldwide is presented comparing income levels and the material composition of residues in several regions. This paper focused on contrasting Brazil and Portugal in terms of waste production and its management from generation to disposal or treatment. Furthermore, it is presented a summary of leading waste-to-energy technologies such as incineration, anaerobic digestion, gasification, pyrolysis, co-combustion, co-gasification, among others. Technical aspects of these thermo-chemical, biological, and physic-chemical processes for the production of biofuels such as biogas, syngas, biodiesel, and hydrogen-enriched gases are presented. Additionally, current aspects of the waste-to-energy market are exposed regarding the major players, investments, and expectations for the future of this activity with the elaboration of SWOT analyses. Finally, a review of greenhouse gases emissions worldwide is presented, specifically from Brazil and Portugal, as well as some consequences of these pollutant gases on the society and the environment and which are the main technologies for carbon dioxide capturing and sequestration as promising solutions for lower pollutant gases concentration in the atmosphere. This review paper aims to provide information for the management of municipal solid waste in Brazil and Portugal considering the mutual objective of meeting sustainable development goals.